2023
DOI: 10.1007/s00418-023-02185-6
|View full text |Cite
|
Sign up to set email alerts
|

Histological study of the role of CD34+ stem cells and mast cells in cyclophosphamide-induced thymic injury in rats and the possible attenuating role of melatonin

Abstract: Cyclophosphamide (CP) is an anticancer drug that adversely affects immunity and thymus structure. Melatonin is a hormone secreted by the pineal gland. It boosts immunity and has antioxidant properties. Therefore, the present study was conducted to investigate the possible protective effect of melatonin on CP-induced changes in the rat thymus. Forty male albino rats were used and divided equally into four main groups. Group I was the control group. Group II (melatonin group) received melatonin at a dose of 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…APH and CP damage the histological structure changes of the rat spleen and thymus, including induction of disorganization in splenic structures, thymic apoptosis, hypocellularity and atrophy ( 35 , 36 ). H&E staining showed that the splenic cord, splenic sinus and trabecula in the red pulp (RP) were displayed clearly in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…APH and CP damage the histological structure changes of the rat spleen and thymus, including induction of disorganization in splenic structures, thymic apoptosis, hypocellularity and atrophy ( 35 , 36 ). H&E staining showed that the splenic cord, splenic sinus and trabecula in the red pulp (RP) were displayed clearly in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…CP probably inhibits cancerous cell proliferation. Studies have also shown that it can cause apoptosis in cancer cells in rat fetuses, lung cells, and, rat thymus (3). Ephedra pachyclada is a plant of the Ephedraceae family.…”
Section: Introductionmentioning
confidence: 99%